The Benefits of Fish Meal in Aquaculture Diets - Richard D. Miles; Frank A. Chapman (EDIS)
FA122, a 7-page fact sheet by R.D. Miles and F.A. Chapman, introduces the reader to this important feed ingredient used in aquaculture as well as swine and poultry production. The authors explain what fish meal is, how it is produced, and its dietary benefits, including high quality protein, amino acid profile, palatability, lipid content, high digestibility, and nutrient content. Additionally the authors address issues of sustainability for the aquaculture industry in the face of increases in worldwide aquaculture production and the demands this will place on commercial fishmeal production. Published by the UF Department of Fisheries and Aquatic Sciences, May 2006.